1987
DOI: 10.1128/jb.169.1.93-96.1987
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and analysis of transcription of the mei2 gene responsible for initiation of meiosis in the fission yeast Schizosaccharomyces pombe

Abstract: We have isolated a hybrid plasmid, pDB(mei2)2, containing a 7.4-kilobases (kb) DNA fragment from a Schizosaccharomyces pombe genomic library which is able to complement the mei2 mutation of S. pombe. Integration of the cloned DNA sequence at the mei2 site on chromosome I demonstrated that it contained the mei2 gene. This gene was localized on a 4.7-kb HindIl-Pvull fragment in the subclone pFMV402. Transcriptional regulation was studied by Northern blot analysis in which polyadenylated RNA was prepared from a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

1988
1988
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 16 publications
1
25
0
1
Order By: Relevance
“…lanes 2 and 8). Starvation-regulated expression of multiple mei2 + transcripts has been previously described (Shimoda et al 1987). Together, these results show that Gcn5, Ada2, and Ada3 act in a common pathway to specifically repress ste11 + and mei2 + expression, suggesting that the HAT module of the SAGA complex negatively regulates mating gene expression in nutrient-rich conditions.…”
Section: Saga and S Pombe Sexual Differentiation Genes And Developmentsupporting
confidence: 53%
“…lanes 2 and 8). Starvation-regulated expression of multiple mei2 + transcripts has been previously described (Shimoda et al 1987). Together, these results show that Gcn5, Ada2, and Ada3 act in a common pathway to specifically repress ste11 + and mei2 + expression, suggesting that the HAT module of the SAGA complex negatively regulates mating gene expression in nutrient-rich conditions.…”
Section: Saga and S Pombe Sexual Differentiation Genes And Developmentsupporting
confidence: 53%
“…Many fission yeast genes responsible for sexual development are transcriptionally induced in response to nitrogen starvation depending on the Ste11 transcription factor (Sugimoto et al, 1991). mei2 is one such gene, and its transcription occurs in a mating-type or pheromone signaling-independent manner (Shimoda et al, 1987). Northern analysis revealed that transcription of mei2 was strongly induced by nitrogen starvation in ste9 cells as well as in wildtype cells (our unpublished results).…”
Section: The Ste9 ؉ Gene Is Essential For G 1 Arrest Upon Starvationmentioning
confidence: 99%
“…Most of Egel's mutants were unable to complete meiosis and failed to produce spores. Egel sent the mutants to Shimoda, whose lab cloned several of the mei and related genes required for ascospore formation (Shimoda et al 1985(Shimoda et al , 1987). …”
Section: S Pombe In Japanmentioning
confidence: 99%